Implementation of Object-Based Learning (OBL) through Taxidermy Collections to Establish 21st Century Skills - Anisa, Nur Lulu; Fithriyanah, Nurul; Umami, Muhimatul (Bioeducation Journal, 2024)
Object-Based Learning (OBL) is an object-based learning that involves the active integration of objects into the learning environment. Object-based learning for students needs to be done, as an effort to grow 21st century skills to face competition in the era of globalization. This study aims to determine the form of learning biology with Object-Based Learning through the collection of animal specimens in the form of taxidermy to cultivate 21st century skills which include cognitive competence, intrapersonal competence and interpersonal competence. The research method uses a qualitative approach with the research population being all 4th semester students majoring in biology majors. Collecting data through observation and filling out questionnaires. Data were analyzed using descriptive and inferential statistical data analysis. The results showed that the students' cognitive competencies included cognitive processes, understanding and creativity with a score of 313 ± 249, while the student responses showed positive results. Thus, Object-Based Learning can be applied to create more active, effective and meaningful learning for students in creating 21st century skills and learning experiences needed by prospective Biology teachers.